The Application of Sports Integrated Psychological Regulation in College English Teaching - Yongjia Huang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Objective: In order to understand the application of psychological regulation in college English teaching, the author proposes a research on the application of sports integrated psychological regulation in college English teaching.The participants in this project are actually two non-English major classes A and B in Level 21, each with 50 students from the School of Sports Business, the final grades of the two classes in the semester before the experiment are equivalent. This experiment used a combination of test paper testing, questionnaire survey, and individual interviews for quantitative and qualitative analysis.Integrating positive psychological intervention into college English teaching can not only improve students' mental health status, at the same time, it also has some help in improving students' English grades.English teachers studying psychology while studying English teaching can help them understand students' psychological factors when learning a foreign language, avoid negative emotions and psychological interference such as boredom and fear towards English, and induce students' positive psychological factors to stimulate their internal motivation for learning. Combining psychological principles with college English teaching can open up new prospects for foreign language teaching and provide effective psychological basis for foreign language teaching work.